Об одном подходе к решению задачи о свободных колебаниях сплошного неоднородного цилиндра конечной длины - Григоренко, А.Я.; Ефимова, Т.Л. (Видавничий дім "Академперіодика" НАН України, 2009)
На базi тривимiрної теорiї пружностi розглянуто задачу про вiльнi коливання суцiльного цилiндра з рiзними граничними умовами на його торцях. Основнi рiвняння теорiї пружностi методом сплайн-апроксимацiї зведено до задачi на власнi значення для систем звичайних диференцiальних рiвнянь по радiальнiй координатi. Розрахунки проводилися стiйким чисельним методом дискретної ортогоналiзацiї. Наведено результати розрахунку частот iзотропного неоднорiдного цилiндра з рiзними умовами на торцях. A problem on natural vibrations of a solid cylinder under various boundary conditions of its endfaces is considered on the basis of 3D elasticity theory. Using the spline-approximation and collocation, the original partial equations of elasticity theory are reduced to the problem for eigenvalues for the high-order systems of ordinary differential equations by the radial coordinate. The problems are solved by the steady-state numerical method of discrete orthogonalization with incremental search. The calculation results are presented for the case of an isotropic inhomogeneous cylinder for different boundary conditions on its end-faces.